Reverse Engineeirng Karakteristik Geometri dan Analisis Fungsi Konfigurasi Golok Koleksi Museum Situs Kepurbakalaan Banten Lama - Wisnu, Ageng Buana; Haryadi, Haryadi; Hendra, Hendra (Politeknik Negeri Padang, 2025)
The research refers to the civilization of manufacturing technology during the Banten Sultanate which carried out metal trade with foreign countries. One of them exported a copper ore to Keling Country and imported scrap iron from Europe. By obtaining the results of the research, it is hoped that it can reveal what manufacturing technology was used, what materials were used in making machete samples and get the usefulness of the research results that can be used. The purpose of this research is to identify the manufacturing process used when making the machete and determine the effect of the configuration on the function of the machete and the strength of the material, determine the effect of the comparison between the modern machete and the museum collection machete and identify the nature of research on the museum collection machete. The method used is a reverse assessment method of a sample of the museum collection's golok. The results obtained are the function of the machete which tends to be in a combination function (attack and control) with a CoG percentage of 35.45 - 41.42% of the overall length of the machete and the manufacturing process used on one of the machetes in the form of casting (cast) with reference to the results of metallographic testing getting nodular cast iron results, with the results of simulations using solidworks giving loading in the lateral and axial directions experiencing stress of 2.936x108 N/m² and 1.541x108 N/m² and a lateral safety factor of 1.2 and axial 2.3.